Pesticide Residues and Health Risk Perceptions of Retail Vegetables in Warri and Environ, Delta State, Nigeria - J. O. Okologume (RESEARCH JOURNAL OF FOOD SCIENCE AND QUALITY CONTROL, 2026)
The rapid growth of urban areas and increased farming practices in cities has raised significant food safety issues, especially concerning chemical contamination of essential foods. This study looked at consumer awareness and health safety perceptions about pesticide residues in commonly consumed leafy vegetables in Warri and Environ, Delta State, Nigeria. Five different types of vegetable types were sampled i.e. bitter leaf (Vernonia amygdalina), African spinach (Amaranthus hybridus), scent leaf (Ocimum gratissimum), fluted pumpkin leaf (Telfairia occidentalis), and waterleaf (Talinum triangulare) from selected major retail markets. The levels of key pesticide residue classes, including herbicides, insecticides, and fungicides were systematically assessed. To understand social and ecological factors, a survey with structured questionnaires was conducted. The survey mapped how vegetables are sourced in retail locations, identified how often they are treated with chemicals, and documented how farmers apply agrochemicals. Potential dietary exposure risks based on international food safety standards set by the FAO, WHO, and NAFDAC were characterized. The study tests showed local build-ups of chemical residues exceeding Maximum Residue Limits (MRLs), indicating possible chronic health risks for regular consumers. Moreover, survey results revealed a concerningly low level of consumer awareness about safety. Public purchasing decisions are mainly influenced by the visible freshness and appearance of the produce, which leaves consumers vulnerable to unnoticed chemical exposure. This study connects foundational data on toxic substances with community risk perceptions. It highlights the urgent need for stricter rules on agrochemical use, standardized farm monitoring, and health awareness campaigns to promote safer vegetable consumption in urban Nigeria.